2013
DOI: 10.1007/s00436-013-3536-7
|View full text |Cite
|
Sign up to set email alerts
|

A rat model to study Blastocytis subtype 1 infections

Abstract: Blastocytis sp. is the most common enteric protozoan in human, but its pathogenesis is still unclear. To study the infectious effects of Blastocytis sp. on tissue damage, we orally challenged the Sprague Dawley (SD) rats with different doses of Blastocytis subtype1 (ST1) and examined the histological changes. We found that there was no difference of disease incidence among the Blastocytis ST1-infected groups challenged with different doses of the protozoan. Histological results showed that the lamina propria w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…The organisms were most commonly identified in the caecum and colon histological sections, which corresponded to the PCR results. There was no associated pathology such as frank inflammation, epithelial damage, mucosal sloughing or lamina propria oedema as has been described previously in experimental animal infectivity models [17], [18], [37]. This lack of pathology was also observed in the preceding study on naturally infected pigs [29].…”
Section: Resultssupporting
confidence: 85%
“…The organisms were most commonly identified in the caecum and colon histological sections, which corresponded to the PCR results. There was no associated pathology such as frank inflammation, epithelial damage, mucosal sloughing or lamina propria oedema as has been described previously in experimental animal infectivity models [17], [18], [37]. This lack of pathology was also observed in the preceding study on naturally infected pigs [29].…”
Section: Resultssupporting
confidence: 85%
“…Regarding ST1 and ST2 isolates, both STs were detected with equal frequency in the symptomatic and asymptomatic groups of our cohort (Chi square test, p = 0.845). However, ST1 was over-represented in groups of symptomatic individuals in previous epidemiological studies in China [59], Turkey [60], Iran [35], Egypt [21], and Lebanon [36]. Moreover, ST1 was the most prevalent ST in some cohorts presenting with IBS [38,61] and was shown to be pathogenic in rat models of blastocystosis [21].…”
Section: Resultsmentioning
confidence: 99%
“…One study highlighted the use of laboratory rats as a good animal model for Blastocystis infection. They showed how rats infected with ST1 showed histopathological changes at all the different doses given and suggested that ST1 infection has pathogenic potential with individual variation [57]. These studies show how animals can be used as a good model for pathogenicity but it is important to take in to consideration that mice are not naturally infected with Blastocystis unlike rats which are commonly found to harbour Blastocystis .…”
Section: Introductionmentioning
confidence: 99%